طرق التحصيل الضريبي و محاربة التهرب الضريبي - خوجة, نادية (My University, 2020)
The aim of studying this topic is the critical importance of the role of tax in developing the economyand the looting and plundering it is exposed to, and highlighting the most important deterrent method, which is tax control and the various means and methods of tax collection. Through the research, we reached the following results, the most important of which are: Building a tax policy based on the existence of effective foundations in order to avoid collision between economic, financial and social objectives. The role and effectiveness of tax information through the statements of the introduction gives the auditor the correct picture of the financial position Tax control is the only deterrent tool that seeks to narrow the circle of evasion, and on the other hand, protect the taxpayer from the arbitrariness of the tax administration.
دراسة حالة لمديرية الضرائب بولاية مستغانم
Keywords: Tax/، evasion ،control fiscal، tax assigned، tax administration